The university of the future’s role in providing humanized and entrepreneurship education for women in Afghanistan - Mohammad Musleh, Islah; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2019)
Despite education is considered as a basic human right, it is been a challenge for the majority of Afghan people especially women. In Afghanistan, women are experiencing various obstacles due to the lack of educational society. They remain poor and deprived of education. Even though during the past couple of decades, there is an increase in initiatives addressing poverty and women education, the majority still suffer. Only 37 percent of women have gained an education. This is due to parents and maybe the government paid less attention to women’s education. This deprivation of women from education caused in the decrease of their role in Governmental affairs and society development. Because of this, they become a burden on their parents and husbands to survive. The aim of this paper is to investigate the main barriers to women education. This paper uses the design and system thinking methodology to understand the main problems and propose a business model of University of the Future (UotF) for a Malaysian university in providing humanizing education to the women in Afghanistan. The contribution of this paper is a conceptual and validated business model in BMC and VPC format. The UotF business model for the Malaysian university proposed in this paper will help Afghan women to gain the basic knowledge, skills and human values in contributing to the wellbeing and development of Afghan society.